2015
DOI: 10.1111/jon.12278
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Reactivity Maps in Patients with Gliomas Using Breath‐Holding BOLD fMRI

Abstract: Background and Purpose To evaluate whether breath-holding (BH) BOLD fMRI can quantify differences in vascular reactivity (VR), as there is a need for improved contrast mechanisms in gliomas. Methods 16 patients (gliomas, grade II=5, III=2, IV=9) were evaluated using the BH paradigm: 4second single deep breath followed by 16seconds of BH and 40seconds of regular breathing for 5 cycles. VR was defined as the difference in BOLD signal between the minimal signal seen at the end of the deep breath and maximal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 44 publications
2
27
0
5
Order By: Relevance
“…These regions have therefore different timing of blood flow arrival than the rest of the brain. These results are in line with previous observations using breath-holding, showing changes in vascular reactivity between different parts of the brain (Geranmayeh et al, 2015;Iranmahboob et al, 2016;Lipp et al, 2015;Tancredi and Hoge, 2013). The motor cortex and pre-central gyrus include representations of the respiratory muscles (Colebatch et al, 1991;Li and Rymer, 2011).…”
Section: Resultssupporting
confidence: 93%
“…These regions have therefore different timing of blood flow arrival than the rest of the brain. These results are in line with previous observations using breath-holding, showing changes in vascular reactivity between different parts of the brain (Geranmayeh et al, 2015;Iranmahboob et al, 2016;Lipp et al, 2015;Tancredi and Hoge, 2013). The motor cortex and pre-central gyrus include representations of the respiratory muscles (Colebatch et al, 1991;Li and Rymer, 2011).…”
Section: Resultssupporting
confidence: 93%
“…Generally, the final step in the cascade involves the vascular response related to regional neuronal activation, and thus most cases of NVU manifest as abnormally decreased or absent regional vascular reactivity within or immediately adjacent to the brain lesion of interest. 49,[59][60][61][62][63] Determining potential NVU increases the clinical utility of fMRI by uncovering false-negative language activations in the eloquent cortex.…”
Section: Breath Hold Taskmentioning
confidence: 99%
“…Mean patient age was 49.3 years 6 15.3 (standard deviation), and no significant difference in age was present between patients with R132H2 and those with R132H+ (P = .75). All tumors in the R132H2 group were histologically astrocytic, while in the R132H+ group, 14 were astrocytic (63%) and five were oligodendroglial (37%). Only one R132H+ tumor exhibited visible enhancement at T1-weighted contrast-enhanced imaging, while only three of the R132H2 tumors (19%) did not show enhancement.…”
Section: Patient Characteristicsmentioning
confidence: 98%
“…Prior to tumor resection, patients underwent standard-of-care structural Blood oxygen level-dependent (BOLD) functional MR imaging is sensitive to glioma-related changes in vascular regulation, as demonstrated in studies showing decreased vascular reactivity in peritumoral tissue during breath holding (13,14) and decreased activation volumes at task-based BOLD functional MR imaging (15)(16)(17). Recently, Chow et al (18) identified an abnormal temporal signature in the unenhanced T2-weighted FLAIR hyperintense peritumoral region in patients with glioblastoma, indicating the presence of infiltration-related vascular dysregulation beyond the margins of identifiable tumor.…”
Section: Image Acquisitionmentioning
confidence: 99%